2009
DOI: 10.1177/0363546509346049
|View full text |Cite
|
Sign up to set email alerts
|

Isometric Placement of Lateral Ulnar Collateral Ligament Reconstructions: A Biomechanical Study

Abstract: The most isometric position for LUCL reconstruction tunnel placement was defined using anatomical references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 21 publications
(52 reference statements)
2
26
1
2
Order By: Relevance
“…The humeral attachment was then completely excised to obtain complete visualization of the capitellum and epicondyle. The proximal-distal length of the radial We calculated the distance from the hCOR to several points using a right elbow to reference a clock face: the 3:00 (anterior) position of the epicondylar mound and the 4:30 position (the point on the epicondylar mound halfway between the anterior and distal edges of the mound at roughly 45 from the central point of the epicondylar prominence); both were similar to points described by Goren et al 8 Distances were also measured from the humeral center of rotation to the junctions of the bone and articular cartilage directly anterior, directly distal, and at 45 distal and anterior.…”
Section: Methodsmentioning
confidence: 64%
“…The humeral attachment was then completely excised to obtain complete visualization of the capitellum and epicondyle. The proximal-distal length of the radial We calculated the distance from the hCOR to several points using a right elbow to reference a clock face: the 3:00 (anterior) position of the epicondylar mound and the 4:30 position (the point on the epicondylar mound halfway between the anterior and distal edges of the mound at roughly 45 from the central point of the epicondylar prominence); both were similar to points described by Goren et al 8 Distances were also measured from the humeral center of rotation to the junctions of the bone and articular cartilage directly anterior, directly distal, and at 45 distal and anterior.…”
Section: Methodsmentioning
confidence: 64%
“…In biomechanical studies, the tunnel should be placed 16-20 mm distal to the radial head 1,2,10,14,19,[21][22][23][24] . On the other hand, Cohen et al suggested that the two bone tunnels should be placed at the proximal margin of the radial head and 15-20 mm distal to it 25) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have shown that reconstruction of the LUCL, such as using tunnels placed in the lateral humeral condyle and the supinator crest of the ulna with tendon grafting, is considerably effective for restoring its stability 2,9,12) . Moreover, biomechanical studies have also indicated that there are no perfectly isometric points along the humerus or ulna for LUCL reconstruction [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Ein Vorteil liegt in der einfachen Entnahmetechnik, ohne den Patienten aus der Seitenlagerung nach diagnostischer Arthroskopie umlagern zu müssen. Obwohl angestrebt, ist eine exakt isometrische Tunnelpositionierung ähn-lich den unterschiedlichen Spannungszuständendes nativenulnarenKollateralbands bei Streckung und Beugung nicht möglich [21]. Eine proximale Fixierung im Drehzentrum des distalen Humerus und eine distale Fixierung 16-20 mm distal der Radiuskopfoberfläche in der Crista supinatoria der Ulna erlaubt dabei eine annähernd isometrische Fixierung [21].…”
Section: Lateraler Bandkomplexunclassified
“…Obwohl angestrebt, ist eine exakt isometrische Tunnelpositionierung ähn-lich den unterschiedlichen Spannungszuständendes nativenulnarenKollateralbands bei Streckung und Beugung nicht möglich [21]. Eine proximale Fixierung im Drehzentrum des distalen Humerus und eine distale Fixierung 16-20 mm distal der Radiuskopfoberfläche in der Crista supinatoria der Ulna erlaubt dabei eine annähernd isometrische Fixierung [21]. Eine genauere anatomische Rekonstruktion der unterschiedlichen Bandanteile des Seitenbandkomplexes ist mit den Doppelstrangtechniken möglich.…”
Section: Lateraler Bandkomplexunclassified